(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: India is an agriculture-based country. The use of organophosphates is rampant for the protection of agricultural products from pests, during growing, storage and sometimes also for ripening. Exposure to pesticides can pose a potential risk to humans. These pesticides are widely used for the production of both vegetables and fruits. Dimethoate is one of the most common Organophosphorus (OP) pesticides sprayed on mangoes.